The role ofmediating effects of user satisfaction and behavioural intention on the influence of the electronic tax system on tax compliance behaviour: An application of bootstrapping technique - Masunga, Faustine Juma; Mapesa, Harun Jeremia; Mwakibete, Andwilile Nyalle; Derefa, Moshi James; Myava, Jema Edmund; Kiria, Joseph Simon (TIJAB (The International Journal of Applied Business), 2026)
The purpose of this study was based on the role of mediating effects of user satisfaction and behavioral intention on the influence of the e-tax system on tax compliance behavior. A mixed-methods approach (sequential explanatory design) was applied where the qualitative findings were used to supplement the results from the quantitative findings. A PLS-SEM technique with SmartPLS 3 was used to analyse data quantitatively while the qualitative data were analysed using thematic analysis. The results revealed that behavioural intention mediates only the relationship between information quality and tax compliance behaviour. When applying multiple mediators, the findings unveiled that service quality and system quality have a significant positive indirect effect on tax compliance behaviour